The Influence of Standard Operational Procedures and Supervision on The Performance of Employees of PT. Swadharma Sarana Informatika Denpasar - I Made Agus Hoki Teges SAKA; Ni Kadek Adinda Putri SUDIVIA; I.B Agung DHARMANEGARA (Journal of Governance, Taxation and Auditing, 2023)
This research aims to determine and analyze the influence of standard operational procedures and supervision on the performance of PT employees. Swadharma Sarana Informatika Denpasar. The population uses PT employees. Swadharma Sarana Informatika Denpasar and a sample of 54 respondents. The data collection methods used are questionnaires, observation, and documentation studies. Data analysis techniques use instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis testing (F and T tests), and coefficient of determination tests (R²). The research results show that standard operational procedures and supervision positively and significantly affect employee performance at PT. Swadharma Sarana Informatika Denpasar, Standard operational procedures positively and significantly affect employee performance at PT. Swadharma Sarana Informatika Denpasar. This means that the more standard operational procedures are improved, the more employee performance at PT will increase. Swadharma Sarana Informatika Denpasar, Supervision positively and significantly affects employee performance at PT. Swadharma Sarana Informatika Denpasar. This means that the more supervision is improved, the more employee performance at PT will increase. Swadharma Sarana Informatika Denpasar.